Lithuanian school mathematical olympiad-2010 - Mačys, Juozas Juvencijus (Lietuvos matematikos rinkinys, 2010)
The texts and answers of the problems of the Lithuanian school mathematical olympiad-2010 are presented. Solutions of several problems are given and discussed.
Keywords: gifted children; mathematical olympiads; problem solving